Constructing sociological student identity through personal branding on TikTok: A study of sociology students at Sriwijaya University - Lisya Septiani Putri; Kurnia Asni Sari; Nabila Tahira; Deska Fitriyani (Priviet Social Sciences Journal, 2026)
The rapid development of social media has created new spaces for individuals to construct and present their identities in digital environments. This study aims to examine how sociology students construct their academic identity through personal branding practices on TikTok, with particular attention to how they translate sociological knowledge, manage self-presentation, and negotiate platform dynamics. A qualitative phenomenological approach was employed, involving in-depth interviews and observations of TikTok accounts belonging to sociology students at Universitas Sriwijaya, who actively produce content related to social issues. The findings reveal that TikTok functions as a digital stage where students strategically construct their academic identities by transforming sociological perspectives into accessible and engaging content. This process involves three interconnected dimensions: the translation of academic knowledge into digital formats, the use of impression-management strategies through language, visuals, and communication styles, and the negotiation between maintaining academic authenticity and adapting to algorithmic visibility. Audience interactions, such as likes, comments, and follower growth, play a significant role in legitimizing the identity performed by students, while algorithmic structures shape how knowledge is presented and distributed. This study concludes that personal branding on TikTok is not merely a form of self-expression but a reflexive and strategic process of identity construction within algorithm-driven public spaces. By highlighting the role of students as emerging intellectual actors, this study contributes to the development of digital sociology, particularly in understanding how academic identity and knowledge dissemination are transformed in contemporary digital culture.